Illegal markets, human trade and transnational organised crime - Nikolić-Ristanović Vesna Ž. (Temida)
In this paper the author explores, focusing largely on the example of the Balkans, the connection between the expansion of neoliberal market economy and war, and related to it the growth of illegal markets and the shadow economy, on one hand, and the victimisation by human trafficking, on the other. By locating human trade within expanding local and global illegal markets, the author is arguing that, without taking into consideration wider social contexts, which create structural incentives for illegal markets and transnational organised crime, we can hardly understand the causes, let alone build effective strategies to combat and prevent it. Consequently, on the basis of the analyses of human trade as a form of both transnational organised crime and illegal markets, some strategies (short-term and long-term) for the prevention and control of human trafficking on both the micro and macro level are suggested.